Effects of COVID-19 Non-Pharmacological Interventions on Dengue Infection: A Systematic Review and Meta-Analysis - Wu, Qin; Dong, Shuwen; Li, Xiaokang; Yi, Boyang; Hu, Huan; Guo, Zhongmin; Lu, Jiahai (Frontiers in Cellular and Infection Microbiology, 2022)
Non-pharmacological interventions (NPIs) implemented during the coronavirus disease 2019 (COVID-19) pandemic have demonstrated significant positive effects on other communicable diseases. Nevertheless, the response for dengue fever has been mixed. To illustrate the real implications of NPIs on dengue transmission and to determine the effective measures for preventing and controlling dengue, we performed a systematic review and meta-analysis of the available global data to summarize the effects comprehensively. We searched Embase, PubMed, and Web of Science in line with PRISMA guidelines from December 31, 2019, to November 1, 2021, for studies of NPI efficacy on dengue infection. To reduce publication bias, we obtained the annual reported dengue cases from highly dengue-endemic countries in 2015–2021 from the European Centre for Disease Prevention and Control to determine the actual change in dengue cases during the COVID-19 pandemic. Random-effects estimate of the pooled odds was generated with the Mantel-Haenszel method. Between-study heterogeneity was assessed using the inconsistency index and subgroup analysis according to country (dengue-endemic or non-endemic) was conducted. This review was registered with PROSPERO (CRD42021291487). A total of 15 articles covering 14 countries or regions were included in the review. Quantitative meta-analysis estimated a pooled relative risk of 0.01 (95% confidence interval [CI]: 0.01–0.01) and 1.06 (95% CI: 1.05–1.07) in dengue non-endemic areas and dengue-endemic countries, respectively, in 2020. The majority of highly dengue-endemic countries reported 0–100% reductions in dengue cases in 2020 compared to previous years, while a few countries reported a dramatic increase. In contrast, there was an obvious reduction in dengue cases in 2021 in almost all countries studied, with an average 55% reduction rate. The overall effectiveness of NPIs on dengue varied with region and time due to multiple factors, but most countries reported significant reductions. Travel-related interventions demonstrated great effectiveness for reducing imported cases of dengue fever. Internal movement restrictions of constantly varying intensity and range are likely to mitigate the entire level of dengue transmission by reducing the spread of dengue fever between regions within a country, which is useful for developing a more comprehensive and sustainable strategy for preventing and controlling dengue fever in the future.